Competitive state anxiety and performance in young female rhythmic gymnasts - Tsopani, D.; Dallas, G.; Skordilis, E. K. (Perceptual and Motor Skills, 2011)
The study was designed to examine the competitive state anxiety and self-confidence of rhythmic gymnasts participating in the Greek national competition. 86 participants, ages 11 and 12 years, completed the Competitive State Anxiety Inventory-2, 1 hr. before competition. The athletes, classified by performance (high and low performance) and participation in the finals (finalists and nonfinalists), responded to the three subscales: Cognitive Anxiety, Somatic Anxiety, and Self-confidence. Analyses indicated differences in Self-confidence between high versus low performance groups and finalists versus nonfinalists. No significant differences were found on Cognitive and Somatic Anxiety. In a regression analysis, Self-confidence was the only significant predictor of performance for this sample. Implications refer to the development of strategies to enhance self-confidence in order to improve the gymnast's performance during competition.